2018
DOI: 10.1111/tbj.12996
|View full text |Cite
|
Sign up to set email alerts
|

Successful cryoablation of breast cancer

Abstract: The current standard of care for screen-detected breast cancers is surgical excision. Cryotherapy is a promising non- surgical alternative treatment for these cancers and is performed under local anesthesia as an outpatient, circumventing the risks that come with an operation. New research also shows promising results for the treatment of breast cancer when cryotherapy is combined with immune modulation as it may help prevent tumor recurrence. We herein report a case of breast cancer treated successfully with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…While the use of cryoablation continues to grow for the treatment of breast cancer, 6,7,[11][12][13][14][15]45,48 there remains a void in the literature surrounding the basic response of breast cancer cells to freezing. Although the exact clinical techniques needed for the complete cryoablation in vivo are difficult to characterize, it is now known that successful cryoablation is dependent on several factors including the cancer phenotype, the number of freezethaw cycles, the rate of cooling and thawing, the final tissue temperature, and the duration of the freezing episode.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While the use of cryoablation continues to grow for the treatment of breast cancer, 6,7,[11][12][13][14][15]45,48 there remains a void in the literature surrounding the basic response of breast cancer cells to freezing. Although the exact clinical techniques needed for the complete cryoablation in vivo are difficult to characterize, it is now known that successful cryoablation is dependent on several factors including the cancer phenotype, the number of freezethaw cycles, the rate of cooling and thawing, the final tissue temperature, and the duration of the freezing episode.…”
Section: Discussionmentioning
confidence: 99%
“…25,30,[54][55][56][57][58] Several reports detailing the successful application of cryoablation to treat breast cancer have appeared in the literature. 6,7,[11][12][13][14][15]59 In a pilot 27-patient study, Sabel et al 59 reported successful ablation of localized breast tumors <1.5 cm in diameter in 100% of the patients. More recently, Simmons et al extended this work in a Phase II clinical study (ACOSOG Z1072) targeting unifocal invasive ductal carcinoma ⩽2.0 cm and reported 100% ablation of tumor <1.0 cm in diameter and 77.4% in tumor ⩾ 1.0 cm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations